FRI0226 Rituximab in rheumatoid arthritis with interstitial lung disease: a multicenter study. (15th June 2017) - Fernández-Díaz, C; Martin-Lopez, M; Carrasco-Cubero, M; Reina-Sanz, D; Rubio-Muñoz, P; Urruticoechea-Arana, A; Miranda-Filloy, J; Vegas-Revenga, N; Dominguez-Casas, L; Gonzalez-Gay, M; Blanco, R
Abstract : Background: Anti-TNFα drugs and several conventional disease-modifying anti-rheumatic drugs (DMARDs) such as methotrexate (MTX) have been involved in the development of Interstitial Lung Disease (ILD). Objectives: Our aim was to assess the efficacy and safety of Rituximab (RTX) in RA patients with ILD. Methods: Multicenter study of RA patients with ILD treated with RTX. ILD was diagnosed by high-resolution computed tomography (HRCT). RTX was used at standard dose (1 gx2 and premedication with iv Methylprednisolone for a six month interval. We assess the the following variables: a) 1-point change in the degree of dyspnea according to the Modified Medical Research Council (MMRC); b) FVC improvement ≥10%; and improvement ≥10% in DLCO; c) radiological changes in HRCT scan, and d) changes in the joint assessment measured by DAS28 score. Results: We studied 18 patients (13 women /5 men) with ILD associated to RA. The mean age±SD was 62.8±11.0 years. The median [IQR] to progression of RA was 5.25 [2–12.8] years. They had received the following DMARDs previously; MTX (n=11), Leflunomide (LFN) (n=9) mycophenolate (MMF) (n=1) sulfasalazine (SSZ) (n=5), hydroxichloroquine (HCQ) (n=4), azathioprine (AZA) (n=1), gold salts (n=1), D-penicillamine (n=1), cyclophosphamide (n=1). 7 patients had previously received biological drugs. RA was seropositive in 16 cases (89%). Besides HRCT, the diagnosis of ILD was confirmed by biopsy in 4 patients. In 2 patients ILD was drug-related: MTX (n=2). RTX was prescribed as monotherapy (n=7) and combined with DMARDs (11. The DMARDs prescribed were: LFD (4), SSZ (2), MTX (3), HCQ (1), AZA (1) MMF (1). A significant improvement of the dyspnea was observed. FVC and HRCT showed an improvement in the period between 6 and 12 months. DLCO remained stable in the majority of the patients (%). DAS28 also improved. After a follow-up of 12 months, the only serious adverse effect was a severe Infection respiratory. Conclusions: RTX seems to be an effective and relatively safe treatment in RA patients with ILD. However, these data should be verified in prospective and randomized studies. Disclosure of Interest: None declared